Strategies employed by EFL doctoral candidates in dissertation writing completion - Saiful Marhaban; Nur Mukminatien; Utami Widiati; Teguh Sulistyo; Wardani Dwi Suhastyanang; Yunita Puspitasari; Asnawi Muslem (Universitas Syiah Kuala, 2021)
This research study aimed at revealing the strategies employed by successful English as a Foreign Language (EFL) doctoral candidates in accomplishing their dissertation writing and their perspectives in association with the stages of research report writing. This is a narrative qualitative inquiry, and the data were collected through an in-depth interview with ten successful EFL fresh graduates who had completed their dissertation writing within six and seven semesters. Using a retrospective technique, the respondents were asked to recall their experiences and activities during the process of writing their dissertation. The results reveal that the successful doctoral candidates used four main strategies of dissertation writing: cognitive, metacognitive, affective, and social strategies. In completing each of the dissertation stages, the doctoral candidates spent much time reading a huge collection of research articles, writing their dissertation on a daily basis, and having intensive consultation with their advisors. This study would be useful for EFL doctoral students to avoid delay in completing their studies and to meet their academic timeline so that they can face their challenging dissertation writing to complete their study on time.